2013
DOI: 10.1155/2013/848049
|View full text |Cite
|
Sign up to set email alerts
|

Comparison ofEnterococcusSpecies Diversity in Marine Water and Wastewater Using Enterolert and EPA Method 1600

Abstract: EPA Method 1600 and Enterolert are used interchangeably to measure Enterococcus for fecal contamination of public beaches, but the methods occasionally produce different results. Here we assess whether these differences are attributable to the selectivity for certain species within the Enterococcus group. Both methods were used to obtain 1279 isolates from 17 environmental samples, including influent and effluent of four wastewater treatment plants, ambient marine water from seven different beaches, and freshw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 29 publications
2
32
1
2
Order By: Relevance
“…E. faecalis is the most common specie isolated from clinical samples (80-90%), interacts with many other organisms and has effects on the environment. In the other hand, E. casseliflavus has been reported in 20% of beach samples and it is associated with natural source, such as plants [31][32][33]. This is consistent with the results found in this research.…”
Section: Resultssupporting
confidence: 92%
“…E. faecalis is the most common specie isolated from clinical samples (80-90%), interacts with many other organisms and has effects on the environment. In the other hand, E. casseliflavus has been reported in 20% of beach samples and it is associated with natural source, such as plants [31][32][33]. This is consistent with the results found in this research.…”
Section: Resultssupporting
confidence: 92%
“…The detection of high numbers of E. casseliflavus in this surface water is similar to findings in some studies but differs from most other studies, as either E. faecalis or E. faecium was reported as the dominant species from surface or other environmental waters (Pinto et al ; Moore et al ; Lata et al ; Luczkiewicz et al ; Lanthier et al ; de et al ). This difference in species distribution could be due to a difference in the isolation method as studies have shown that difference in media and incubation temperatures could select for certain Enterococcus species (Jackson et al ; Ferguson et al ). The difference in species distribution could also be the result of the regional difference as Moore et al (2008) detected different Enterococcus species distribution at separate locations based on the structure of the waterbody and the presence of potential contamination sources.…”
Section: Discussionmentioning
confidence: 99%
“…Kinzelman et al (2003) reported the inability to culture and verify enterococcus from Enterolert wells was a drawback with the method. In a method comparison study, Ferguson et al (2013) found that the Enterolert method yielded a higher percentage of non-Enterococcus organisms in surface-water samples than the membrane filtration method on mEI agar. Because of the potential for observing falsepositive results and the added time and cost for verifying Enterolert wells, together with the limitation of a 100-mL sample volume, the mEI method may be more advantageous for analyzing groundwater samples for enterococci than the Enterolert method.…”
Section: Discussionmentioning
confidence: 99%